Spatial Transformation in Central Weda Industrial Expansion, Land-Use Change, and Settlement Dynamics in Indonesia’s Nickel Frontier - Alhadar, Nabila Islamaiya; Husni, Ibrahim; Ariyanto, Ariyanto; Musa, Abdul Haris (Fakultas Teknik Universitas Khairun, 2025)
The Indonesia Weda Bay Industrial Park (IWIP) has rapidly transformed Central Weda District’s spatial structure between 2012 and 2022. This paper integrates satellite-based land-use change analysis, regional statistics, spatial plan (RTRW/RDTR) review, field survey summaries, and carrying-capacity computations to evaluate the impacts of industrial agglomeration on land conversion, housing pressure, tenure dynamics, and ecological buffer integrity. Results (from local datasets) show settlements increased from 39.3 ha (2012) to 82.2 ha (2022), while industrial area expanded to 16,000 ha. Industrial employment rose from 650 (2018) to 29,800 (2022), fueling a nearly 400% increase in local land prices (e.g., Lelilef Sawai: IDR 50,000/m² - IDR 277,000/m²). Carrying capacity calculations indicate most villages retain DDPm 1 (sufficient capacity) except Lelilef Sawai (DDPm 1), which already exceeds sustainable settlement thresholds. The paper concludes with policy recommendations for zoning enforcement, ecological buffer protection, worker housing programs, and integrated industrial-regional planning.